2020
DOI: 10.1101/2020.06.16.20133041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of specimen types and saliva stabilization solutions for SARS-CoV-2 testing

Abstract: Identifying SARS-CoV-2 infections through aggressive diagnostic testing remains critical in tracking and curbing the spread of the COVID-19 pandemic. Collection of nasopharyngeal swabs (NPS), the preferred sample type for SARS-CoV-2 detection, has become difficult due to the dramatic increase in testing and consequential supply strain. Therefore, alternative specimen types have been investigated, that provide similar detection sensitivity with reduced health care exposure and potential for self-collection. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 29 publications
6
45
0
Order By: Relevance
“…Combined with untested concerns regarding SARS-CoV-2 RNA stability in saliva, supplements to reduce degradation and improve sample processing have become common. Prior work from saliva samples, however, has indicated that some buffers optimized for host nucleic acid stabilization may actually inhibit viral RNA detection, 4 - 6 particularly in extraction-free PCR workflows. 7 Thus, if true saliva - which is relatively easy to pipette - is being tested, the utility of collecting saliva in expensive tubes containing purported stabilization buffers comes into question.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with untested concerns regarding SARS-CoV-2 RNA stability in saliva, supplements to reduce degradation and improve sample processing have become common. Prior work from saliva samples, however, has indicated that some buffers optimized for host nucleic acid stabilization may actually inhibit viral RNA detection, 4 - 6 particularly in extraction-free PCR workflows. 7 Thus, if true saliva - which is relatively easy to pipette - is being tested, the utility of collecting saliva in expensive tubes containing purported stabilization buffers comes into question.…”
Section: Introductionmentioning
confidence: 99%
“…One hundred forty-nine papers were considered for inclusion; of these, 19 studies comprising 21 cohorts met inclusion criteria ( Supplemental Figure S1 ). A brief summary of the studies included in this review may be found in Table 1 , and a brief discussion of each paper (including the results used in this review) is presented in the Supplemental Appendix S1 3 , 4 , 5 , 6 , 7 , 8 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 . Twelve of the included cohorts involved 100 or more patients.…”
Section: Resultsmentioning
confidence: 99%
“…Equivocal results and assay failures were not used in the calculation of sensitivity, nor in the construction of the CRS for each study. Confidence limits for sensitivity were computed using Newcombe’s efficient score method 16 as implemented in the Vassarstats Clinical Calculator 1 ( http://vassarstats.net/ )( Table 1 ) 3 , 4 , 5 , 6 , 7 , 8 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 . Criteria for performing a formal meta-analysis were as follows: 1) studies used the same amplification technology [such as RT-PCR]; 2) studies used the same upper airway sample site (AN, MT and NP could be included together, but not admixed with studies based on OP samples; 3) studies enrolled a similar patient mix (e.g., symptomatic, asymptomatic, hospitalized) and similar clinical environment (drive-through/ community health center or hospital).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al showed that saliva had a higher detection rate (88.09%) for SARS-CoV-2 in comparison to throat swabs (45.24%) and NPS (76.19%) [171]. While most studies have found saliva to be as sensitive as NPS for COVID-19 diagnostic tests [54,179,180], few have reported slightly lower sensitivity [181].…”
Section: Salivamentioning
confidence: 99%